Quiz Maker with Audit Log System for SK Pintas Puding - Zarul Syah Imran Zulkifli; Ahmad Khalid, Shamsul Kamal (Applied Information Technology And Computer Science, 2023)
Online Quiz has been created as an approach for students and teachers to have an assessment for every student. The problems come with the integrity of the students answering the quiz. While teacher may not notice the behavior of the student answering the online quiz, student may misbehave and try to find the answer via online search engine.Quiz Maker With Audit Log System comes to aid with the additional security feature which is audit logs. It helps to track the user action on the web system itself. Quiz Maker With Audit Log System For SK Pintas Puding is created using PHP language with the hashing of BCRYPT algorithm. The system passed all (100%) security checklist planned for the system including user authentication, audit logs, hashed and salted stored password and several criticalfunctional tests.